Filming reality : the independent documentary movement in India - Shoma A. Chatterji (Sage, 2015)
Filming Reality explores the independent documentary film movement in India post-1970s, when it began to acquire an identity of its own and many films got worldwide recognition. It analyses notable documentaries made over the last four decades, including those by iconic film-makers such as Satyajit Ray, Mani Kaul, Anand Patwardhan; activists such as Rakesh Sharma, Ranjan Palit, Amar Kanwar; feminists such as Deepa Dhanraj and Madhusree Dutta; and auteurs such as Sanjay Kak, R.V. Ramani and others. Featuring a compilation and analysis of noted and rare documentaries, this book is of immense value to film buffs, film scholars and film-makers.